التحالف الاستراتيجي: استراتيجية مقترحة للتعليم الجامعي أثناء جائحة كورونا وما بعدها - أبو تجار، هبة محمد محمد (جامعة المنصورة - مركز تطوير الأداء الجامعي, 2021)
استهدف البحث الحالي تقديم استراتيجية مقترحة للتحالف الاستراتيجي بين الجامعات المصرية لتعزيز قدرتها على تقديم نظام تعليمي أفضل أثناء جائحة كورونا وفي أعقابها، حيث تعتبر التحالفات الحل الأمثل لمشكلات الجامعات في جميع المواقف والظروف. وقد اقتضى ذلك التعرف على الإطار المفاهيمي للتحالف الاستراتيجي، وتحليل البيئة الداخلية للتعليم الجامعي أثناء جائحة كورونا لبيان أهم نقاط قوته وضعفه، وتحليل البيئة الخارجية لاستشراف أهم الفرص التي تتيحها، وأهم التحديات التي تفرضها. وصولا إلى ملامح الاستراتيجية المقترحة ومتطلبات تنفيذها. ولتحقيق ذلك تم استخدام المنهج الوصفي، وأسلوب التحليل البيئي (swot) كأحد أساليب التخطيط الاستراتيجي. The current research aimed to present a proposed strategy for the strategic alliance between Egyptian universities to enhance their ability to provide a better educational system during and in the after of the Corona pandemic, as alliances are considered the best solution to university problems in all situations and circumstances. This required identifying the conceptual framework of the strategic alliance, analyzing the internal environment of university education during the Corona pandemic to show its most important strengths and weaknesses, and analyzing the external environment to explore the most important opportunities it offers, and the most important challenges it poses. To the features of the proposed strategy and the requirements for its implementation. To achieve this, the descriptive approach and the environmental analysis method (SWOT) were used as one of the strategic planning methods.
Keywords: الأمراض الوبائية -- استراتيجيات التعليم -- التعليم الإلكتروني -- جائحة كورونا "كوفيد-19"